Bloom - Oppel, Kenneth, 1967- (Oppel, Kenneth, 1967- Overthrow, 2020)
"The first book in a can't-put-it-down, can't-read-it-fast-enough action-thriller trilogy that's part Hatchet, part Little Shop of Horrors! The invasion begins--but not as you'd expect. It begins with rain. Rain that carries seeds. Seeds that sprout--overnight, everywhere. These new plants take over crop fields, twine up houses, burrow below streets. They bloom--and release toxic pollens. They bloom--and form venus-fly-trap like pods that swallow animals and people. They bloom--everywhere, unstoppable. Or are they? Three kids on a remote island seem immune to the toxic plants. Anaya, Petra, Seth. They each have strange allergies--and yet not to these plants. What's their secret? Can they somehow be the key to fighting back this invasion? They'd better figure it out fast, because it's starting to rain again...." --